Kairo, Ägypten: Die Goldbleche aus dem Grab des Tutanchamun - Bertsch, Julia; Broschat, Katja; Eckmann, Christian (e-Forschungsberichte des DAI, 2023)
The project centers on approx. 100 decorated gold sheet appliqués from the tomb of Tutankhamun (14th century BC). Since their discovery by Howard Carter in 1922, these objects have been stored in the magazines of the Egyptian Museum in Cairo without ever being restored or studied scientifically. Therefore, the project aims at the conservation, the archaeological, technological, and archaeometrical analyses, as well as the iconographical study of this important but previously little considered group of objects.